The Use of Tiktok Based on Audiolingual Method in Arabic Learning at an Islamic Junior High School in Indonesia - Hadi Saputra; Danial Hilmi; Syukran syukran (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2023)
There have been various discussions on the use of TikTok in Arabic learning today, and they indicate that it has the potential as an interactive learning media. However, using TikTok in Audiolingual-based Arabic learning needs more attention. Therefore, this research aims to fill the gap by describing the utilization, stages, and supporting and inhibiting factors in using TikTok in Arabic learning based on an Audiolingual approach at an Islamic Junior High School in Indonesia. This study used descriptive qualitative research. The researcher carried out observations and interviews to obtain research data. The research data were analyzed using the Miles and Huberman technique. The results of this study report that 1) the use of TikTok in learning Arabic is based on media support, teaching skills, and variations in delivery. 2) There are three stages in the learning process: preparation, implementation, and evaluation. 3) Supporting factors found are students' ability to understand lessons and adequate school facilities. The inhibiting factor is the limited time available for applying the audiolingual method, which takes quite a long time and makes students feel bored. This study recommends research on the effectiveness of TikTok on interest, motivation, and achievement in learning Arabic.